Depression, its correlates and quality of life of undergraduate medical students in the Kumaon region of Uttarakhand state, India - Solanki, Hariom Kumar; Awasthi, Sadhana; Kaur, Amandeep; Pamei, Gaihemlung (Indian Journal of Community Health, 2021)
Background: Medical students are future health care providers and experience a lot of stress during their training years. They are more likely to suffer depressive disorders than the general population and have a poorer quality of life. Objectives: To determine the prevalence of depressive disorder, its correlates and quality of life of medical students studying at a medical college in North India. Methods and material: It was a cross sectional study which included all the students enrolled at the study medical college. Data was collected using pre-validated questionnaires namely - 20 item ‘Center for Epidemiologic Studies Depression Scale (CES-D)’, WHO Quality of life (QoL) – BREF questionnaire and ‘Smartphone Addition Scale - Short version’ (SAS-SV) questionnaire to assess for depression, quality of life and smartphone addiction respectively which was distributed in the classroom to be filled. Multivariate logistic regression was employed to ascertain association between depression and the other variables. Results: The study had an effective response rate of 79%. Using a score of 16 or above as cut-off on CES-D scale145 study participants (36.7%) were found to be depressed. Participants who negatively compared themselves with their peers/friends and also those who were addicted to smartphone were significantly more likely to be depressed [1.85(1.12-3.05) and 1.96 (1.29-2.97) respectively]. We report a statistically significant negative relationship between physical domain score [0.97(0.95-0.99)], psychological domain score [0.95(0.93-0.97)] and social relationship domain score [0.97(0.95-0.99)] on BREF Quality of life questionnaire and the presence of depression among the study participants. Conclusion: The prevalence of depression among medical students was high and those with depression have significantly poor quality of life.